Tratamiento de las medidas coercitivas reales por las fiscalías penales corporativas de Maynas para el aseguramiento de la reparación civil - año 2019 - Alegría Osco, Arturo Guido (2024)
At the end of the criminal procedure, the jurisdictional body issues a sentence, that in many cases imposes a penalty, civil reparation and other accessory sanctions. This research sought to determine if the treatment of thereal coercive measures in the Fiscal District of Loreto, helped to ensure the payment of civil reparations, understood as the compensation of the damage caused by the perpetrator to the victim, in fact, in practice, it is not ensured from the beginning of the process, because the real coercive measures are not considered, making it easier for the defendant or civilly responsible third party to dispose of his patrimony, in order to disengage himself from his pecuniary obligation. With this purpose, the present research was developed as a Quantitative- Basic - Applied - Descriptive – Explanatory type. A structured survey was applied to a sample of 33 legal professionals per variable (magistrates of the Provincial Criminal Corporate Prosecutor's Offices of Maynas), who gave as a result that, it is the duty of the Public Ministry to ensure the payment of the Civil Reparation; but, in 2019, this duty wasn´t evidenced in results, due to the low number of requests for real coercive measures, because there was a lack of investigative acts (at the preliminary and preparatory level), aimed at the investigation of assets and/or rights of the accused and/or civilly responsible third parties; similarly, it was warned that the procedural norm does not define in a clear and precise manner the material presuppositions of each one of the real coercive measures, and that in 2019 there was an overloaded fiscal work.